Effectiveness of donning and doffing personal protective equipment education using video debriefing among Korean undergraduate nursing students - GyeJeong Yeom; Jiyun Park (BMC, 2024)
Abstract Background The use of appropriate personal protective equipment (PPE) in healthcare settings is a very important factor of infection control activities to prevent transmission of infection. In this study, we aimed to develop a non-face-to-face method that can reduce transmission of infection and an educational method that allows self-learning and self-training, and verify the effectiveness of a donning and doffing PPE education using video debriefing on third-year nursing students in clinical train. Methods The researcher assigned groups through random sampling using a random number table from the list of research subjects who agreed to participate. Therefore, 35 subjects in the experimental group with an education on donning and doffing PPE using video debriefing and 34 subjects in the control group with video-based training (VBT) were participated in April 2023 at a university in Incheon, South Korea. The evaluation phase involved verifying effects of the education on observer evaluation donningand doffing PPE performance and self-evaluation donningand doffing PPE performance. Satisfaction with the education also assessed immediately after intervention by the experimental group. Results The experimental group had significantly higher scores for observer evaluationdonning (t = 7.84, p < .001) and observer evaluation doffing (t = 6.52, p < .001) PPE performances than the control group. However, there was no significant difference in self-evaluation donning (t = 0.98, p < .330) or doffing PPE performance (t = 0.17, p < .869) between the two groups. In the experimental group that applied video debriefing, learning satisfaction was 4.33 ± 0.82 points out of 5 points. Conclusions The education on donning and doffing PPE applying video debriefing was effective. If the education developed in this study is used as a self-learning method to improve the infection control capacity necessary to respond to a disaster crisis caused by infectious diseases, it is considered to be useful for preventing the transmission of infectious diseases in the future.